Antibacterial and Antifungal Activity of Clove Extract (Syzygium Aromaticum): Review - Nathaniel Hiwandika; Susana Elya Sudrajat; Ika Rahayu (HM Publisher, 2021)
Cloves is one of the native Indonesian plants and is used in many aspects of life. Cloves are used in multiple industries and as detergents, soaps, perfumes, food seasonings, aromatherapy, etc. Cloves are mainly used for ingredients in kretek cigarettes in Indonesia. Various studies of cloves reported they have good pharmacological and therapeutic effects. The main compounds of clove extract are eugenol and β-caryophyllene, which are powerful antibacterial and antifungal agents. The clove ethanolic extract showed the activity to inhibit Gram-positive and negative bacteria such as B. cereus, S. aureus, E. coli, P. aeruginosa, S. pneumonia, S. aureus,S. epidermidis, A. hydrophila, K. pneumoniae, P. gingivalis, and P. mirabilis . Clove essential oil has shown the ability to inhibit the growth of V. inaequalis, C. Albicans, C. glabrata, and C. tropicalis. Cloves extract can be used as an essential ingredient in various medicines. However, it requires further research and trials.